Contribution of Inflammation and Bone Destruction to Pain in Arthritis: A Study in Murine Glucose‐6‐Phosphate Isomerase–Induced Arthritis. Issue 12 (9th November 2019) - Ebbinghaus, Matthias; Müller, Sylvia; Segond von Banchet, Gisela; Eitner, Annett; Wank, Isabel; Hess, Andreas; Hilger, Ingrid; Kamradt, Thomas; Schaible, Hans‐Georg
Abstract : Objective: Arthritis is often characterized by inflammation and bone destruction. This study was undertaken to investigate the contribution of inflammation and bone destruction to pain. Methods: Inflammation, bone resorption, pain‐related behaviors, and molecular markers (activating transcription factor 3 [ATF‐3], p‐CREB, and transient receptor potential vanilloid channel 1) in sensory neurons were measured in murine glucose‐6‐phosphate isomerase (G6PI)–induced arthritis, a model of rheumatoid arthritis. Depletion of Treg cells before immunization changed self‐limiting arthritis into nonremitting arthritis with pronounced bone destruction. Zoledronic acid (ZA) was administered to reduce bone resorption. Results: Compared to nondepleted mice, Treg cell–depleted mice exhibited arthritis with more severe bone destruction and higher guarding scores ( P < 0.05; n = 10 mice per group) as well as more persistent thermal hyperalgesia ( P < 0.05), but displayed similar mechanical hyperalgesia at the hindpaws (n = 18–26 mice per group). These pain‐related behaviors, as well as an up‐regulation of the neuronal injury marker ATF‐3 in sensory neurons (studied in 39 mice), appeared before the clinical score (inflammation) became positive and persisted in Treg cell–depleted and nondepleted mice. In the late stage of arthritis, Treg cell–depleted mice treated with ZA showed less bone resorption (<50%; P < 0.01) and less thermal hyperalgesia ( P < 0.01) than Treg cell–depleted mice without ZA treatment (n = 15 mice per group), but ZA treatment did not reduce the clinical score and local mechanical hyperalgesia. Conclusion: Pain‐related behaviors precede and outlast self‐limiting arthritis. In nonremitting arthritis with enhanced bone destruction, mainly local thermal, but not local mechanical, hyperalgesia was aggravated. The up‐regulation of ATF‐3 indicates an early and persisting affection of sensory neurons by G6PI‐induced arthritis.